Exploring the writing process of Indonesian EFL students: the effectiveness of think-aloud protocol - Abas, Imelda Hermilinda; Abd Aziz, Noor Hashima (Australian International Academic Centre, Australia, 2016)
The objectives of this study were to explore the writing process of the Indonesian English as a Foreign Language (EFL) students and to find out the effectiveness of using think-aloud protocol to understand the writing process.The data were obtained from six proficient EFL students who were doing Postgraduate English Language Studies Program in Indonesia.The participants were selected based on the following criteria: had completed a minimum of two academic writing courses, had written a thesis in English, had taught English for more than two years and considered as proficient writers based on IELTS result. The finding of the study showed that all of the participants went through the following writing process: prewriting, planning, drafting, pausing, reading, revising, editing and publishing.In addition, the think-aloud protocol had different effects on the participants. ive of the participants admitted that the think-aloud protocol had a positive effect because it helped them in organizing their thoughts and ideas. However, only one participant found thinking aloud made her difficult to focus on the writing task due to the demand to verbalize and write at the same time.